Genomic characterization of large rearrangements of the LDLR gene in Czech patients with familial hypercholesterolemia - Fajkus Jiří; Soška Vladimír; Letocha Ondřej; Zapletalová Petra; Freiberger Tomáš; Tichý Lukáš; Goldmann Radan; Fajkusová Lenka (BMC, 2010)
Abstract Background Mutations in the LDLR gene are the most frequent cause of Familial hypercholesterolemia, an autosomal dominant disease characterised by elevated concentrations of LDL in blood plasma. In many populations, large genomic rearrangements account for approximately 10% of mutations in the LDLR gene. Methods DNA diagnostics of large genomic rearrangements was based on Multiple Ligation dependent Probe Amplification (MLPA). Subsequent analyses of deletion and duplication breakpoints were performed using long-range PCR, PCR, and DNA sequencing. Results In set of 1441 unrelated FH patients, large genomic rearrangements were found in 37 probands. Eight different types of rearrangements were detected, from them 6 types were novel, not described so far. In all rearrangements, we characterized their exact extent and breakpoint sequences. Conclusions Sequence analysis of deletion and duplication breakpoints indicates that intrachromatid non-allelic homologous recombination (NAHR) between Alu elements is involved in 6 events, while a non-homologous end joining (NHEJ) is implicated in 2 rearrangements. Our study thus describes for the first time NHEJ as a mechanism involved in genomic rearrangements in the LDLR gene.